ANÁLISIS PSICOMÉTRICO PRELIMINAR DE LA ESCALA PERFIL DE IMPACTO EMOCIONAL COVID-19 EN UNIVERSITARIOS PERUANOS - Rodríguez de los Ríos, Luis (2020)
The instrumental psychometric qualities of the Emotional Impact Profile COVID-19 (García Pérez & Magaz, 2020) are analyzed and established in this instrumental study (Ato, López-García, & Benavente, 2013), in order to use it posteriori in the university student population in relation to the emotional impact generated by the effects of this virus in the Lima population. In a sample of 161 university students (117M; 44V) of an average age of 23 years (RIQ = 3), a virtual Profile form was administered, estimating the validity by analyzing its internal structure using a confirmatory factor analysis (AFC), intercorrelating the items of the five scales of the Profile: anger / resentment, fear, anxiety, stress and depression, with the polychoric coefficient and using the Weighted Least Square Mean and Variance Adjusted (WLSMV) estimator. The resulting indices show an excellent empirical typified fit between the theoretical structure of the Profile and the data collected (χ² = 426.83, gl = 265, CFI = .970, TLI = .966, RMSEA = .062, SRMR = .079). On the other hand, the reliability of the five scales calculated by the alpha and omega coefficients, yielded high results (> .85). These excellent psychometric qualities endorse the use of the Profile in research processes on emotional effects of COVID-19.